2001
DOI: 10.1161/hy1201.097305
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase Gene Polymorphism and Maternal Vascular Adaptation to Pregnancy

Abstract: Abstract-A common polymorphism of the endothelial NO synthase gene that predicts a Glu298Asp amino acid substitution in the mature protein has been associated with cardiovascular disorders in which NO bioactivity is impaired. However, the influence of this polymorphism on endothelial function is unknown. Healthy pregnancy is associated with enhanced endothelium-dependent, flow-mediated dilation (FMD) of the brachial artery, a response mediated by NO. In this study, we investigated the effect of the endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 52 publications
1
57
2
Order By: Relevance
“…Mechanistic studies indicated that this substitution alters function. For instance, associations have been described between this polymorphism and eNOS activity (11,33) or endothelial function (34,35). A mechanism by which eNOS Glu298Asp might reduce NO bioavailability has also been reported.…”
Section: Discussionmentioning
confidence: 97%
“…Mechanistic studies indicated that this substitution alters function. For instance, associations have been described between this polymorphism and eNOS activity (11,33) or endothelial function (34,35). A mechanism by which eNOS Glu298Asp might reduce NO bioavailability has also been reported.…”
Section: Discussionmentioning
confidence: 97%
“…This reduction is reportedly associated with various vascular diseases such as myocardial infarction (Shimasaki et al, 1998), placental abruption (Yoshimura et al, 2001), and pre-eclampsia (Yoshimura et al, 2000;Savvidou et al, 2001). A meta-analysis has revealed a close association between rs1799983 and idiopathic RM (Su et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that healthy pregnant women who carried the common Glu298Asp polymorphism in eNOS gene had reduced flow-mediated dilatation of the brachial artery, an NO-dependent response. 33 More recently, we showed that an impairment in the endothelial function is an early feature of women who subsequently developed preeclampsia. 27 Thus, these findings suggest that women homozygous for the Asp298 allele generate low NO in vivo and may be more susceptible to endothelial dysfunction.…”
Section: Serrano Et Al Enos Polymorphisms and Preeclampsia 705mentioning
confidence: 98%
“…41 The current study supports the hypothesis that endothelial dysfunction attributable to decreased NO bioavailability plays a role in the pathogenesis of preeclampsia. 27,33 …”
Section: Perspectivesmentioning
confidence: 99%